Sloth - Wasserstein, Wendy (The seven deadly sins, 2005)
Here is a rollicking parody of the self-help genre, one that skewers the couch-bound, apathetic mentality so pervasive in America today. With tongue in cheek, Sloth guides readers step-by-step toward a life of noncommittal inertia. "You have the right to be lazy," writes Wasserstein. "You can choose not to respond. You can choose not to move." Readers will find out the importance of Lethargiosis--the process of eliminating energy and drive, the vital first step in becoming a sloth. To help you attain the perfect state of indolent bliss, the book offers a wealth of self-help aids. Readers will find the sloth songbook, sloth breakfast bars (packed with sugar, additives, and a delicious touch of Ambien), sloth documentaries (such as the author's 12-hour epic on Thomas Aquinas), and the sloth network, channel 823, programming guaranteed not to stimulate or challenge in any way. ("It may be difficult to distinguish between this and other channels, but only on channel 823 can you watch me sleeping.") Readers will also learn the top ten lies about Sloth, the ten commandments of Sloth, the SLOTH mantra, even the "too-much ten"--Over-achievers such as Marie Curie, Shakespeare, and William the Conqueror. You will discover how to become a sloth in your diet, exercise, work, and even love-life (true love leads to passion, she warns, and passion is the biggest enemy of sloth). Wendy Wasserstein is one of America's great comic writers--one who always has a serious point to her humor. Here, as she pokes fun at the self-help industry, she also satirizes the legion of Americans who are cultural and political sloths. -- From publisher description